PENERAPAN LEADER MEMBER EXCHANGE DALAM PENDIDIKAN KEJURUAN - Hartanto, Suryo (JURNAL DIMENSI, 2014)
This article, proposed to change a patterns and the concept of leadership in vocational education. Vocational Leadership   still have a  political tendency   or specific social groups, the selected leader  which do not possess the skill and competence of course, the problem occur are unconducive of  organizations school, hampered individual career and skill, organization school is no longer running on educational track, this very inhibited  development of vocational education. The proposed concept is leader member exchange  theory or LMX. Basic concept of Leader Member Exchange are mutual trust, mutual respect and taking charge in developing of organization, it is considered suitable to be applied in vocational education.